The operational benefits of ERP adoption by third-party logistics organisations in South Africa . - Chetty, Nishalen Gavin (My University, 2016)
The prevalence of ERP systems in 3PL organisations internationally has grown over the past decade and as a result, has filtered into the South African market because of the associations with these multinational logistics organisations. There has been a significant amount of research conducted to understand the factors that contribute toward the success and/or failures of ERP system implementations within the sector. However, the operational benefits as perceived by the operational and IT staff has not been studied in great detail. This research focused on the perceived operational benefits of ERP implementation as perceived by operational and IT staff that were actually involved in the adoption process. The data collection was qualitative and stemmed from in-depth interviews of senior management staff. These management staff had operational and IT portfolios within their respective organisations. The interviews were used to establish their perceived operational benefits of ERP implementations pre and post the adoption process in order to ascertain if any operational benefits were realised. The interview process was also used to understand the influence of end user capability to realise the operational benefits. The findings that were obtained indicated that many of the operational benefits that were realised were similar to the perceived benefits prior to the implementation and adoption process as per the operational and IT management staff that were involved and that the end-user capability influenced those benefits. There were, however, challenges encountered when adopting ERP systems due to financial and time constraints of these organisations, which need to be recognised. The perceived operational benefits are often the product of experience or prior learnings. The reality is that ERP system implementations have a high rate of failure and the effects are often detrimental to organisations. The concise understanding of operational benefits and the influence that the end user has to realise those benefits can be valuable to organisations considering adopting ERP systems or moving to more complex systems. The results of this research should provide a better understanding of the implications for organisations that do not factor in the influence of end users to impact the operational benefits of ERP systems. The findings of the study also highlight the fact that strategies, visions and goals of companies are seldom communicated throughout the whole organisation, leading to tunnel views in divisions and departments. Efficiencies could be enhanced in line with the overall strategies, visions and goals if these could be reviewed and disseminated regularly at all levels as to their application on a hands-on basis for all systems and processes.
MBA Thesis
Keywords: Business enterprises -- Computer networks -- Management,Business logistics,Data processing,Management information systems.